Risk Factors of Colorectal Carcinoma Incidence in Young Adults: A Meta-Analysis - Putranto, Agi Satria; Julistian, Julistian (UI Scholars Hub, 2019)
Introduction. The incidence and mortality of colorectal cancer (CRC) in young adults (below the age of 50 years) has been increased. However, there’s no screening method for these cancer in those group of age because there isno scientifically proven risk factor. Thus, a meta-analysis carried out to find out the risk factor for CRC in young adults. Method. A Meta-analysis study was conducted in January 2017. Literature search addressed to the articles published during a period of 2007– 2017 in Cochrane and PubMed using keywords: “young” AND “risk factor” AND “colorectal cancer” OR “colon cancer” or “rectal cancer”. Inclusion criteria were the CRC prevalence, risk factor analysis for CRC incidence and young population (below 50 years old). The meta-analysis carried out through qualitative and quantitative approach. Results. In the last 10 years, there were twelve published articles met the criteria. Those were cohort study (an article), case–control study (four articles), and cross–sectional study (seven articles). Twenty–five risk factors were noted. The meta–analysis showed that gender (males) with OR = 1.66, 95% CI = (1.04–2.64); I2 = 93%), family history with OR = 2.01, 95% CI = (1.11–3.67); I2 = 78%), metabolic syndrome with OR = 1.80, 95% CI = (1.49–2.16), I2 = 0%), and smoking with OR = 1.57, 95% CI = (1.40–1.77), I2 = 4%) were the significant risk factors with the association of CRC. Conclusion. Young adults of males, with a family history of CRC, metabolic syndrome, and smoking were at the risk to have colorectal cancer